2005
DOI: 10.1152/japplphysiol.00323.2005
|View full text |Cite
|
Sign up to set email alerts
|

Exercise flow-volume loops in prepubescent aerobically trained children

Abstract: We studied mechanical ventilatory constraints in 13 aerobically trained (Tr) and 11 untrained (UT) prepubescent children by plotting the exercise flow-volume (F-V) loops within the maximal F-V loop (MFVL) measured at rest. The MFVL allowed to determine forced vital capacity (FVC) and maximal expiratory flows. Expiratory and inspiratory reserve volumes relative to FVC (ERV/FVC and IRV/FVC, respectively) were measured during a progressive exercise test until exhaustion. Breathing reserve (BR) and expiratory flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…accurate measurement of VO 2 max, children present a substantial challenge; not least of which is the high prevalence of EFL in this population (28,29,40). One approach has been to estimate VO 2 max indirectly from submaximal tests whereas another has been to accept secondary criteria (e.g., HR, RER) to provide confidence that VO 2 max has been achieved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…accurate measurement of VO 2 max, children present a substantial challenge; not least of which is the high prevalence of EFL in this population (28,29,40). One approach has been to estimate VO 2 max indirectly from submaximal tests whereas another has been to accept secondary criteria (e.g., HR, RER) to provide confidence that VO 2 max has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically children have smaller airways in comparison with lung size than adults (24) which, combined with greater ventilations at any given metabolic rate, leads to a high prevalence of EFL irrespective of VO 2 max per se (28,29,40). EFL leads to dynamic hyperinflation (40) thereby mechanically disadvantaging the inspiratory muscles and increasing the likelihood of respiratory muscle fatigue which has been documented in adults during high intensity exercise (20).…”
Section: Efl In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the airways occasionally do present a significant limitation to expiratory airflow resulting in dynamic hyperinflation, increased respiratory muscle work andV E limitation during heavy-intensity exercise. Healthy subjects most susceptible to mechanical airway limitations to expiratory flow during heavy exercise include fit prepubescent children (251), fit aging adults with reduced lung elastic recoil (185) and highly fit young adult females (229,230). In the latter group, it was shown that theV E response to inhaled CO 2 (via rebreathing) decreased in slope at heavy-intensity exercise (vs. rest or mild exercise), coincident with evidence of expiratory flow limitation.…”
Section: Mechanical Constraints On Ventilation During Heavy Intensitymentioning
confidence: 99%
“…Children involved in high levels of physical activity tend to have larger maximal flow-volume loops (FVLs) than untrained children at comparable ages and body size (393). Moreover, several studies have reported an increase in static lung volumes, over that expected from the age-dependent increase in stature, with long-term swim training (32,152,586), running training (146), and additional physical education (477).…”
Section: Physical Training Across the Lifespanmentioning
confidence: 99%